TINDAK TUTUR MEMERINTAH PADA AYAT-AYAT ALQURAN PERIODE MAKKAH - Hanifullah Syukri; Miftah Nugroho; Bakdal Ginanjar (Haluan Sastra Budaya, 2020)
The holy book is an important thing as an object of research study, especially in the field of linguistics. This study aims to describe the directive speech acts governing the verses of the Qur'an during the Mecca period. This type of research used in this research is descriptive analytical qualitative, which describes in detail and in depth the directive directive speech acts contained in the verses of the Koran of the Mecca period. The object of this research is the embodiment of directive speech acts in the Qur'anic verses of the Makkah period. The data source of this research is Al-Qur'an Karim. This research data is in the form of lingual units contained in the verses of the Koran of the Mecca period in which there are directive directive speech acts. Data collection techniques are done by listening and note taking. Data analysis was carried out by linking the texts of the Qur'anic verses of the Makkah period to the surrounding contexts. The findings of this research are directive directive speech acts contained in the verses of the Koran of the Mecca period found as many as 1043. It shows that directive directive speech acts are directive speech acts that are dominant in the verses of the Qur'anic period of Mecca so that it can be said that directive speech acts rule is the most able to change the state of jahiliyyah society into a better and orderly society.